Clinical implications of arterial hypertension in patients with spontaneous coronary artery dissection. Issue 2 (March 2022) - Alfonso, Fernando; García-Guimaraes, Marcos; Alvarado, Teresa; Sanz-Ruiz, Ricardo; Roura, Gerard; Amat-Santos, Ignacio J.; Abdul-Jawad Altisent, Omar; Tizón-Marcos, Helena; Flores-Ríos, Xacobe; Masotti, Mónica; Pérez-de Prado, Armando; Ferre, Georgina Fuentes; et al.
Abstract : Background: Spontaneous coronary artery dissection (SCAD) is a rare but increasingly recognized cause of acute coronary syndrome. Many patients with SCAD have associated coronary risk factors. However, the implications of arterial hypertension in SCAD patients remain unknown. Objective: This study sought to assess the clinical implications of arterial hypertension in a nationwide cohort of patients with SCAD. Methods: The Spanish SCAD registry (NCT03607981) prospectively enrolled 318 consecutive patients. All coronary angiograms were centrally analyzed to confirm the diagnosis of SCAD. Patients were classified according to the presence of arterial hypertension. Results: One-hundred eighteen patients (37%) had a diagnosis of arterial hypertension. Hypertensive SCAD patients were older (60 ± 12 vs. 51 ± 9 years old) and had more frequently dyslipidemia (56 vs. 23%) and diabetes (9 vs. 3%) but were less frequently smokers (15 vs. 35%) than normotensive SCAD patients (all P < 0.05). Most patients in both groups were female (90 vs. 87%, NS) and female patients with hypertension were more frequently postmenopausal (70 vs. 47%, P < 0.05). Hypertensive SCAD patients had more severe lesions and more frequently multivessel involvement (15 vs. 7%, P < 0.05) and coronary ectasia (19 vs. 7%, P < 0.05) but showed a similar prevalence of coronary tortuosity (34 vs. 26%, NS). Revascularization requirement was similar in both groups (17 vs. 26%, NS) but procedural success was significantly lower (65 vs. 88%, P < 0.05) and procedural-related complications more frequent (65 vs. 41%, P < 0.05) in SCAD patients with hypertension. Conclusion: Patients with SCAD and hypertension are older, more frequently postmenopausal and have more coronary risk factors than normotensive SCAD patients. During revascularization SCAD patients with hypertension obtain poorer results and have a higher risk of procedural-related complications (NCT03607981).